An ESTs description of the new Vanin gene family conserved from fly to human. - Granjeaud, S.; Naquet, P.; Galland, F. (Immunogenetics, 1999)
Circulation and tissue colonization are essential properties of lymphoid cells and involve major families of adhesion molecules (e.g. , integrin, selectin, mucin-like, and molecules from the immunoglobulin superfamily). The mouse Vanin-1 molecule was recently identified and found to be involved in the colonization of the thymus by hematopoietic precursor cells. Here we show based on computational analysis of EST sequence database resources that Vanin-1 belongs to a new family of related molecules present from drosophila to human. This family includes the amidase enzyme Biotinidase, and a central protein domain is shared between Vanin and Nitrilase families, suggesting that Vanin molecules might bear an enzymatic activity. Five of these molecules were new uncharacterized cDNA sequences only described as ESTs. The three human Vanin genes map to the same region of Chromosome 6q. The detailed results are consultable at the VANIN web page (http://tagc. univ-mrs.fr/pub/vanin/).